Perancangan Alat Bantu Pengecekan Fuse Box dengan Menggunakan Metode Quality Function Deployment - M Yani Syafei; Natasyashinta Liviadrianne (JIE Scientific Journal on Research and Application of Industrial System, 2018)
ABSTRACTPT. XYZ is a company engaged in automotive for motorcycles and car vehicle. The increasing number of product demand from customers requires companies to provide the best service, especially the quality of the product itself. The company often gets a lot of consumer complaints against Fuse Box X products that are not function on the busbar A and busbar B when are assembled by the customer in the last 3 months from March to May 2017.Based on the problem, the authors propose the need for the holding of checking tools that are able to detect that Busbar A and Busbar B are mounted tightly on Fuse Box X products. The method used to analyze consumer needs, one of them is by using QFD. Based on the HOQ obtained three criteria of the largest technical response is to remove the sound from the 12 Volt Buzzer, detect the product with LED lights, and electric components tightly sealed by PVC casing. Then it be done the design process of checking tool Fuse Box X and testing tool.By using hypothesis test of two independent population proportions stated defect proportion decreased by 34.78% after using Fuse Box X checking tool, where the value of 6.11% smaller than the previous (without checking tool) was 40.89%.Keywords: Checking tools, Quality Function Deployment, Design, Fuse Box X.